Autonomic dysfunction in autism: The roles of anxiety, depression, and stress. (April 2021) - Taylor, Emily C; Livingston, Lucy A; Callan, Mitchell J; Ashwin, Chris; Shah, Punit
Autism spectrum disorder (ASD) is associated with atypical autonomic nervous system (ANS) function. However, little is known about this relationship, while accounting for co-occurring mental health conditions (e.g. anxiety) that are also associated with ANS dysfunction. In addition, research on the ANS has typically involved physiological measurements, without using more clinically meaningful measures of ANS dysfunction, such as the self-reported frequency of ANS-related physical health symptoms. Furthermore, very little is known about ANS function in autistic adults, given that previous research has focused on ANS dysfunction in children with ASD. Addressing these gaps in the literature, we compared ANS function in adults with(out) ASD (Study 1). Although autistic adults reported greater ANS dysfunction than matched neurotypical controls, this difference was not significant after controlling for anxiety and depression. Similarly, in a large nonclinical sample (Study 2), we found that anxiety and stress mediated the relationship between autistic traits and ANS dysfunction. Together, we conclude that ANS dysfunction is not a feature of ASD per se, but instead attributable to the high levels of anxiety and stress in autistic adults. We discuss the clinical relevance of these findings for managing ANS dysfunction and other physical and mental health concerns in autistic adulthood. Lay abstract: The autonomic nervous system (ANS) is responsible for the functioning of the heart, bladder, pupils and several other bodily functions. Therefore, when the ANS functions abnormally, individuals can experience a number of physical symptoms, including dizziness, abnormal sweating and digestive difficulties. Currently, it is unclear if autistic adults experience ANS dysfunction. Therefore, in this study, we investigated whether autistic adults report more ANS-related physical symptoms, indicating greater ANS dysfunction, and whether this may be related to autism, or rather anxiety, depression, or stress. The findings suggest that ANS dysfunction, where found in autism, is due to co-occurring stress and anxiety. We therefore propose that treating stress and anxiety may be an effective way to ameliorate ANS-related health problems in autistic adults.